Investigation of the in vitro α-glucosidase and α-amylase Inhibitory and Antioxidant Effects of Oxalis corniculata Linn Roots for Antidiabetic Applications - Thi Van Anh, Nguyen; The Hai, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: This study was carried out to evaluate the anti-diabetic and antioxidant potential of extract fractions from the roots of Yellow Wood Sorrel ( Oxalis corniculata Linn.). Results demonstrated that all fractions (crude methanol, n-hexane, ethyl acetate - EA, and water) exhibited inhibitory activity against two key carbohydrate-digesting enzymes, α-glucosidase and α-amylase. Notably, the EA fraction (OCR.EA) displayed the most potent activity, with IC 50 values of 135.0 µg/mL and 28.0 µg/mL, respectively, significantly superior to the reference drug acarbose (IC 50 of 168.5 µg/mL and 31.8 µg/mL, respectively). Concurrently, the EA fraction also possessed remarkably strong antioxidant activity in both DPPH and ABTS assays, particularly in the ABTS test with an IC 50 of 0.31 µg/mL, outperforming the standard antioxidants trolox and ascorbic acid. These findings confirm the dual advantage of the EA fraction from O. corniculata roots, not only in postprandial blood glucose control via enzyme inhibition but also in mitigating oxidative stress, a key factor in preventing diabetic complications. This discovery opens a promising research direction for developing natural herbal-based supplementary products for diabetes management. Keywords: α-amylase, α-glucosidase, Antioxidant, Oxalis corniculata, and Roots .